Energetically expensive dynamo action in Earth’s basal magma ocean - Nathanaël Schaeffer; Stéphane Labrosse; Jonathan M. Aurnou (Proceedings of the National Academy of Sciences, 2025)
Previous studies focusing on the electrical conductivity and thermal evolution of an early magma ocean at the base of Earth’s mantle have found that basal magma ocean (BMO) convection could have produced the ancient geomagnetic field. By advances in high-resolution dynamo modeling, we find that convection in a thin BMO-like spherical shell is able to sustain strong magnetic fields, including axial dipolar fields similar to current day field structure. However, integrating our dynamo results with improved thermal evolution models and taking the planet’s rapid rotation into account using rotating convective turbulence models implies that an Earth-like magnetic field was unlikely to have been generated in the BMO, a finding relevant to the interpretation of ancient paleomagnetic signatures, Earth’s global-scale dynamics, and long-term planetary evolution. Large uncertainties still remain, calling for refined models of deep Earth thermal and mineralogical processes, accurate determination of prefactors in convective scaling laws, and fully coupled core-BMO dynamo simulations. Nonetheless, our work highlights that BMO-type dynamos intrinsically require a larger product of electrical conductivity and velocity than core-type dynamos, and that they are similarly rotationally constrained, so that velocities are significantly reduced compared to nonrotating estimates.